An overview of healthcare improvement: unpacking the complexity for clinicians and managers in a learning health system. Issue 10 (2nd October 2020) - Melder, Angela; Robinson, Tracy; McLoughlin, Ian; Iedema, Rick; Teede, Helena
Abstract: Given the pace of technological advancement and government mandates for healthcare and system transformation, there is an imperative for change. Health systems are highly complex in their design, networks and interacting components, and experience demonstrates that change is very challenging to enact, sustain and scale. Policy‐makers, academics and clinicians all need better insight into the nature of this complexity and an understanding of the evidence‐base that can support healthcare improvement (HCI), or quality improvement, interventions and make them more effective in driving change. The evidence base demonstrates the vital role of clinical engagement and leadership in HCI, and it is imperative that clinicians engage to improve front‐line healthcare. The literature on HCI is vast, applies different and inconsistent terminology and encompasses often loosely defined and overlapping concepts. An increasingly broad range of disciplines has contributed to the available evidence base, but often discipline‐specific perspectives frame these contributions. Available literature can also be overly driven by the generation of theoretical concepts and the advancement of academic understanding. It does not necessarily primarily provide focussed and pragmatic insights to guide and inform frontline practice. We aim to address these issues by summarising theories, frameworks, models and success factors for improvement in complex health systems to assist clinicians and others to engage and lead change. We integrate the field of HCI into the learning health system highlighting the key role of the clinician. We seek to inform stakeholders; clinicians and managers to guide the planning, enacting, sustaining and scaling of HCI.